Software Testing Techniques and Tools: A Review - Sukaina Izzat; Nada N. Saleem (College of Education for Pure Sciences, 2023)
The software development process is closely related to the creation and evaluation processes. The problem with this software development is that it often lacks testing which leads to software failures. In order To maintain a high quality product in excellent performance condition, testing becomes critical. The software can be tested by using White Box, Black-Box, or Gray testing techniques. In this investigation, the types of tests were reviewed. Performing Testing with White Box Testing uses a number of testing methodologies based on path testing, including the production of flowcharts, cyclomatic complexity assessment, and independent path testing. As a result, it is possible to implement a foundation path testing technique and white box approach to testing. This review included several axes, namely the definition of white box testing tools, then the testing techniques in general, the benefits and gains of each of these technologies, the levels of testing, and finally the steps of conducting the test. This review then came to several conclusions that are mentioned at the end of this paper.